(untitled) (South Asian Journal of Agriculture, 2019)
The present investigation involves study of variability and genetic diversity of few developmental characters such as date of maximum flower per plant (DMF), number of seeds per plant (NSPP) and seed weight per plant (SWPP) in blackgram (Vigna mungo L.). These three quantitative characters were studied in 24 lines and three years under different environmental conditions. The model proposed by Perkins and Jinks was followed in this study. In the analysis, greater portion of total phenotypic variation (s2p) appeared to be due to the environmental variations (s2e). The highest heritability (h2 b) (0.8181) was found for SWPP, while the highest genetic advance (G.A.=172.5508), high genetic advance of percentage (G.A.%=332.5627) and high genetic co-efficient of variability (G.C.V.=161.4381) were estimated in NSPP. The present investigation deals with the analysis of phenotypic, genotypic and environmental co-efficient of variability, range, mean with standard error, heritability (in broad sense), genetic advance and genetic advance of percentage. Genetic co-efficient of variability was very much pronounced and varied from treatment to treatment, year to year and lines to lines for all the characters, which indicates that the characters were quantitative in nature and under polygenic control. Therefore, further research would be undertaken for improving the characters of this pulse. South Asian J. Agric., 7(1&2): 1-5